A Cross-Cultural Comparison of the Role of Sexual Objectification in the Relationship Between Alcohol Use and Sexual Assault Perpetration - Tuliao, Antover P. (Journal of interpersonal violence, 2021)
In this study, we examined how sexual objectification can help explicate the relationship between alcohol use and sexual assault perpetration. Specifically, we examined a mediation and a moderation model. Moreover, given that gender roles and sexual norms vary across cultures, we also examined the structural invariance of the models between a U.S. male (n = 404) and Philippines male (n = 100) college sample. Path analyses were used to examine the mediation and the moderation model, and multiple groups analysis was utilized to examine model differences between samples. Sexual objectification fully mediated the relationship between alcohol use severity and sexual aggression. Furthermore, the mediation model was invariant between the U.S. sample and Philippines sample. A significant alcohol use severity by sexual objectification interaction effect was found for both samples. Simple slopes analysis indicated that alcohol use severity was not associated with sexual aggression among those with high sexual objectification scores. Among men with low sexual objectification scores, alcohol use severity was associated with higher likelihood toward sexual assault. For the Filipino sample, the impact of alcohol consumption on sexual aggression is more pronounced compared with the U.S. sample. Sexual objectification is a key variable in understanding the alcohol use—sexual aggression relationship. Country differences in alcohol use, cultural meanings of Filipino masculinity, and sexual norms and behaviors accounts for noninvariance in the moderation model. Implications for sexual assault reduction programs were also discussed.